The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1073/pnas.2120083119
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing encodes functional intracellular CD59 isoforms that mediate insulin secretion and are down-regulated in diabetic islets

Abstract: Significance This project describes the existence of previously unknown non–GPI-anchored CD59 isoforms required for insulin secretion, named CD59–IRIS-1 and CD59–IRIS-2, and finds reduced expression of CD59-IRIS isoforms in human diabetic islets, showing a link between dysregulation of IRIS isoforms and defects in insulin secretion in diabetic patients. These data open a path for future studies into CD59-IRIS expression and function in additional cell types capable of regulated secretion. Identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…139 Moreover, emerging research has indicated the complosome's capacity to regulate insulin production within pancreatic β-cells, particularly influenced by CD59 and C3. 141,142,157 Such observations underscore the complosome's involvement in diabetes, a primary instigator of NAFLD. In addition to that, in the development of atherosclerosis, a close metabolic disorder to NAFLD, cell-intrinsic C5a-C5aR1 axis in monocytes and macrophages has been reported as a crucial contributor in a high-fat diet-induced mouse model.…”
Section: Evidence Linking Complosome Dysregulation To Nafld Pathogenesismentioning
confidence: 87%
See 1 more Smart Citation
“…139 Moreover, emerging research has indicated the complosome's capacity to regulate insulin production within pancreatic β-cells, particularly influenced by CD59 and C3. 141,142,157 Such observations underscore the complosome's involvement in diabetes, a primary instigator of NAFLD. In addition to that, in the development of atherosclerosis, a close metabolic disorder to NAFLD, cell-intrinsic C5a-C5aR1 axis in monocytes and macrophages has been reported as a crucial contributor in a high-fat diet-induced mouse model.…”
Section: Evidence Linking Complosome Dysregulation To Nafld Pathogenesismentioning
confidence: 87%
“…Additionally, intracellular C3 stimulates the assembly and secretion of very low‐density lipoprotein, thereby reducing lipid accumulation in hepatocytes 139 . Moreover, emerging research has indicated the complosome's capacity to regulate insulin production within pancreatic β‐cells, particularly influenced by CD59 and C3 141,142,157 . Such observations underscore the complosome's involvement in diabetes, a primary instigator of NAFLD.…”
Section: The Complosome and Nafldmentioning
confidence: 99%
“…2). In a similar fashion, the insulin secretion‐supporting intracellular form of CD59 is also generated via alternative splicing of the same gene that normally encodes cell‐surface CD59 [73].…”
Section: Intracellular Complement—the Complosome—and Its Activitiesmentioning
confidence: 99%
“…CD59 is more susceptible to glucose-dependent nonenzymatic glycation-inactivation in DM. Autoantibodies against glycosylated proteins initiate complement activation again via classical pathways [ 132 ].…”
Section: Common Mechanisms Of Dvcsmentioning
confidence: 99%